Two-Sided Wave Generation in a High-Order Spectral Numerical Wave Tank - Aertsens, Tim; Ducrozet, Guillaume; Toffoli, Alessandro; Monbaliu, Jaak (Volume 5: Ocean Engineering, 2023)
International audience Abstract The Coastal & Ocean Basin (COB) is a brand-new wave-current basin in Ostend (Belgium). The basin is 30m long and 30m wide, and it is equipped with modular wavemakers on two adjacent sides. This allows generation of multi-modal seas (including the so-called crossing-sea states). A system of multiple pumps will also be installed to allow generation of currents propagating at an arbitrary angle relative to the dominant wave field. To optimally utilize this new facility, an efficient numerical equivalent of the COB has been coded based on the High-Order Spectral Method (HOSM). The first step is the addition of a secondary wavemaker to the open-source High-Order Spectral Numerical Wave Tank (HOS-NWT). This was done by calculating an additional potential for each of the wavemakers in two separate additional domains and then using them as forcing terms on the two sides of the basin where the physical wavemakers are present. The implementation was done in a generic way and is made open-source. The effectiveness of the implemented method is demonstrated by comparing three base cases: only the x-wavemaker, only the y-wavemakers and both wavemakers together. However, there still remain challenges when it comes to wave generation in the y-direction and accurately modelling the corner between the two wavemakers.